Rhodium‐Catalyzed Highly Diastereo‐ and Enantioselective Synthesis of a Configurationally Stable S‐Shaped Double Helicene‐Like Molecule. Issue 27 (30th April 2020) - Kinoshita, Suzuka; Yamano, Ryota; Shibata, Yu; Tanaka, Yusuke; Hanada, Kyoichi; Matsumoto, Takashi; Miyamoto, Kazunori; Muranaka, Atsuya; Uchiyama, Masanobu; Tanaka, Ken
Abstract: An S‐shaped double helicene‐like molecule (>99 % ee ), possessing stable helical chirality, has been synthesized by the rhodium(I)/difluorphos complex‐catalyzed highly diastereo‐ and enantioselective intramolecular double [2+2+2] cycloaddition of a 2‐naphthol‐ and benzene‐linked hexayne. The collision between two terminal naphthalene rings destabilizes the helical chirality of the S‐shaped double helicene‐like molecule, but the introduction of two additional fused benzene rings significantly increases the configurational stability. Thus, no epimerization and racemization were observed even at 100 °C. The enantiopure S‐shaped double helicene‐like molecule forms a trimer through the multiple C−H⋅⋅⋅π and C−H⋅⋅⋅O interactions in the solid‐state. The trimers stack to form columnar packing structures, in which neighboring stacks have opposite dipole directions. The accumulation of helical structures in the same direction in the S‐shaped double helicene‐like molecule enhanced the chiroptical properties. Abstract : The diastereo‐ and enantioselective synthesis of a configurationally stable S‐shaped double helicene‐like molecule has been achieved with the excellent ee value of >99 % by the rhodium(I)/difluorphos complex‐catalyzed intramolecular double [2+2+2] cycloaddition of a 2‐naphthol‐ and benzene‐linked hexayne.